The first insight into Acanthocephalus (Palaeacanthocephala) satellitome: species-specific satellites as potential cytogenetic markers - Anna Marková; Martina Orosová; Pablo Mora; Michal Benovics; Pedro Lorite (Scientific Reports)
Abstract Acanthocephalan parasites are often overlooked in many areas of research, and satellitome and cytogenetic analyzes are no exception. The species of the genus Acanthocephalus are known for their very small chromosomes with ambiguous morphology, which makes karyotyping difficult. In this study, we performed the first satellitome analysis of three Acanthocephalus species to identify species- and chromosome-specific satellites that could serve as cytogenetic markers. RepeatExplorer2 revealed a remarkably high number of species-specific repeats, with a predominance of satellite DNAs, alongside variations in repetitive content between sexes. Five satellites in A. anguillae, two in A. lucii and six in A. ranae were successfully mapped to chromosomes using FISH. Each satellite showed a clustered hybridization signal at specific chromosomal locations, which allowed us to create a schematic representation of the distribution of satellites for each species. These newly identified satellites proved to be useful chromosomal markers for the accurate identification of homologous chromosome pairs. No FISH-positive signals were observed on the supernumerary chromosomes of A. anguillae and A. lucii, supporting the hypothesis that these chromosomes have recent origin.